Managing Students to Build Discipline : A Case Study At Islamic Senior High School, Islamic Centre - Mukhlisoh, Mukhlisoh; Durtam, Durtam; Liana, Vina Putri; Fatihah, Imroatul (IAIN Syekh Nurjati Cirebon, 2025)
This research is motivated by the still low level of student discipline at MA Islamic Centre Cirebon Regency, which is evident from the high number of violations against school regulations. This study aims to describe: Student management, Discipline level, and the role of student management in improving student discipline. The method used is qualitative with a descriptive approach. Data were collected through semi-structured interviews, observations, and documentation. Data analysis was conducted by grouping information from sources and organizing it into themes that align with the research objectives. The research results indicate that student management at MA Islamic Centre has been running well, marked by various development efforts such as new student orientation, morning assemblies, and the imposition of sanctions for violations. However, factors such as lack of student motivation and environmental influences hinder the improvement of discipline. The data sources include the Head of the Madrasah, the Deputy Head of Student Affairs, teachers, and students. Data analysis techniques include collection, presentation, and conclusion drawing. The results show that overall, student management significantly contributes to improving student discipline through structured and consistent coaching activities.